Digital twins for internal combustion engines: A brief review - Viet Dung Tran; Prabhakar Sharma; Lan Huong Nguyen (BIORE Scientia Academy, 2023)
The adoption of digital twin technology in the realm of internal combustion (IC) engines has been attracting a lot of interest. This review article offers a comprehensive summary of digital twin applications and effects in the IC engine arena. Digital twins, which are virtual counterparts of real-world engines, allow for real-time monitoring, diagnostics, and predictive modeling, resulting in improved design, development, and operating efficiency. This abstract digs into the creation of a full virtual depiction of IC engines using data-driven models, physics-based simulations, and IoT sensor data. The study looks at how digital twins can potentially be used throughout the engine's lifespan, including design validation, performance optimization, and condition-based maintenance. This paper emphasizes the critical role of digital twins in revolutionizing IC engine operations, resulting in enhanced reliability, decreased downtime, and enhanced emissions control through a methodical analysis of significant case studies and innovations.